1997
DOI: 10.1002/zamm.19970770712
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Nonlinear Localization in a Flexible Structure with Vibro‐Impacts

Abstract: In this work a numerical and experimental study of nonlinear motion confinement phenomena in a nonlinear flexible assembly with vibro‐impacts is carried out. The assembly consists of two coupled cantilever beams whose motion is constrained by rigid barriers. In the theoretical model the impact nonlinearities are simulated by clearance nonlinearities with steep stiffness characteristics; special care is taken to model energy dissipation due to inelastic impacts. The theoretical results confirm that the vibro‐im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Axially vibrating beams with or without distributed elastic constraints have been considered in [22,23] by following a stochastic or deterministic approach, respectively. Nonlinear problems have been studied only recently [24,25]; in particular the existence of localized nonlinear normal modes has been proved in [26][27][28]. In [26] it has been observed that the origin of nonlinear mode localization in lumped-mass periodic systems is the dependence of the frequencies of substructures on their vibration amplitude; thus nonlinearities cause mistuning and localization takes place even in perfectly periodic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Axially vibrating beams with or without distributed elastic constraints have been considered in [22,23] by following a stochastic or deterministic approach, respectively. Nonlinear problems have been studied only recently [24,25]; in particular the existence of localized nonlinear normal modes has been proved in [26][27][28]. In [26] it has been observed that the origin of nonlinear mode localization in lumped-mass periodic systems is the dependence of the frequencies of substructures on their vibration amplitude; thus nonlinearities cause mistuning and localization takes place even in perfectly periodic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the system are shown in Table 1. These parameters are the same as those of the beam used to experimentally study localization in a coupled system in a previous work [18]. The #exural rigidity is EI, the linear mass density m and the length is¸.…”
Section: Clamped Beam With Non-linear Springsmentioning
confidence: 97%
“…It is advisable to employ double-precision computations throughout to reduce the numerical inaccuracies as much as possible. The number of K}L modes used (p) should be in accordance with equation (18). For the want of enhanced accuracy, the higher K}L modes should not be carelessly used as some of them are spurious and would lead to numerical instabilities.…”
Section: P(u T)"k ? U Cmentioning
confidence: 98%
See 1 more Smart Citation
“…(4)- (6). All the random variables are defined in a probability space (Θ, F , P) (A) Parametric probabilistic model of data uncertainties for the non-linear term.…”
Section: Probabilistic Modelling Of Uncertaintiesmentioning
confidence: 99%